Impact of humic acids on EYL liposome membranes: ESR method - Pytel Barbara; Filipiak Aneta; Pisarek Izabella; Olchawa Ryszard; Man Dariusz (Nukleonika, 2015)
In this paper, the effects of model (commercial) and natural (extracted from peat) humic substances on the membrane of liposomes formed with egg yolk lecithin (EYL) are presented. In our research, mass concentrations of fulvic and humic acids were used, which in relation to lecithin varied from 0% to 13%. To study membrane fluidity, electron spin resonance (EPR) was used with two spin probes, penetrating various regions of the lipid bilayer. The effects of model and natural humic substances (humic acids – HAs and fulvic acids – FAs) on the lipid membrane in different regions were researched: the lipid-water interphase, and in the middle of the lipid bilayer. It was shown that FA and HA impact the fluidity of liposome membranes in different ways. Increased mass concentrations of HAs decreased membrane fluidity in both acids: extracted from peat and the model. However, increased mass concentration of FAs extracted from peat, decreased membrane fluidity in the surface region, at the same time stiffening the central part of the bilayer. Increasing the concentration of FAs extracted from peat had the opposite effect when compared to model FA. This effect may be related to the complexation of xenobiotics present in the soil environment and their impact on biological membranes.